Annotated bibliography of the Russian literature on glaciology for 2014 - V. M. Kotlyakov; L. P. Chernova (Лëд и снег)
The proposed annual bibliography continues annotated lists of the Russian-language literature on glaciology that were regularly published in the past. It includes 271 references grouped into the following ten sections: 1) general issues of glaciology; 2) physics and chemistry of ice; 3) atmospheric ice; 4) snow cover; 5) avalanches and glacial mudflows; 6) sea ice; 7) river and lake ice; 8) icings and ground ice; 9) the glaciers and ice caps; 10) palaeoglaciology. In addition to the works of the current year, some works of earlier years are added, that, for various reasons, were not included in previous bibliographies.